Penyusunan Laporan Keuangan Dalam Rangka Pelaksanaan Program Kerja KKN Tematik MBKM di Desa Laweyan Probolinggo - Nurhidayah Nurhidayah; Acynthia Ayu Wilasittha (Community : Jurnal Pengabdian Pada Masyarakat, 2023)
In realizing the role of students as agents of change, Kuliah Kerja Nyata Tematik Merdeka Belajar Kampus Merdeka (KKNT MBKM) program was held. The KKNT MBKM program is expected to be able to solve problems and advance the community by developing an area and increasing income, through programs that have been created by KKNT group 60 students. This service journal aims to find out the budget needed in each work program carried out by KKNT MBKM UPN Veteran East Java students in Laweyan Probolinggo Village. From the results of the cash receipt and expenditure report, it proves that there is no cash left and shows that the amount of expenditure for work programs is less than the amount of expenditure for the agenda, which is 41 59% with details of 24% for the UMKM ramadhan bazaar, 1% for NIB, 31% for bamboo craft workshops and 3% for branding UMKM products.